The Total Light Process : New & Selected Poems - Hall, James Baker, 1935-2009 (Book collections on Project MUSE., 2004)
Nationally acclaimed poet, photographer, filmmaker, and novelist James Baker Hall has long been regarded as one of Kentucky's most profound artists. Hall's growing body of work is an essential part of Kentucky's literary tradition, and yet his poetry in particular transcends the borders of the Commonwealth. The Total Light Process collects poems spanning Hall's celebrated career as well as new poems that have never before been published. The subjects of Hall's poems range from humorous and revealing portraits of his fellow writers and friends Wendell Berry, Ed McClanahan, and Gurney Norman, t.